2018
DOI: 10.21890/ijres.382934
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Middle School Mathematics Teachers’ Perceptions of the Standards for Mathematical Practice by Textbook Type

Abstract: . (2018). U.S. middle school mathematics teachers' perceptions of the standards for mathematical practice by textbook type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…While there are a number of studies on how mathematics teachers have implemented the CCSS-M mathematical practices (e.g., Davis et al, 2013;Selling, 2016), we found little research on science teachers' understanding and/or implementation of the NGSS practice of using mathematics and computational thinking. A few studies focus on what PSTs learn as a result of courses that target some aspect of this particular practice; these studies report mixed success in helping PSTs understand and implement mathematics and computational thinking.…”
Section: Review Of Relevant Literaturementioning
confidence: 76%
“…While there are a number of studies on how mathematics teachers have implemented the CCSS-M mathematical practices (e.g., Davis et al, 2013;Selling, 2016), we found little research on science teachers' understanding and/or implementation of the NGSS practice of using mathematics and computational thinking. A few studies focus on what PSTs learn as a result of courses that target some aspect of this particular practice; these studies report mixed success in helping PSTs understand and implement mathematics and computational thinking.…”
Section: Review Of Relevant Literaturementioning
confidence: 76%
“…Students and teachers of mathematics need to engage with the mathematical practice daily actively. According to Davis et al (2018), middle mathematics teachers' knowledge and understandings of the standards for mathematical practice are limited and will require more training regarding the use of the standards. The selection of appropriate curricular resources can enhance teachers' knowledge of the standard and affect its use (Davis et al, 2017).…”
Section: Teacher's Role In Implementing the Standardsmentioning
confidence: 99%
“…Kruse et al (2017) found a lack of observable evidence of mathematics teachers implementing the standards for mathematical practice in Grades 4 through 12. When investigating the implementation of the use of the standards for mathematical practice in middle school, Davis et al (2018) found that one in three middle school mathematics teachers struggles in naming the eight standards for mathematical practice despite having training on the standards. The literature does not address how teachers perceive they use the standards and the supports they may need to make a shift in their practice (Kruse et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
“…In addition to an increased focus on research involving the mathematical practices over the past decade (e.g., Bernander et al, 2020;Bleiler et al, 2015;Bostic & Matney, 2014;Davis et al, 2018), there exists extensive research pertaining to those processes (National Council of Teachers of Mathematics [NCTM], 2000) and proficiencies (National Research Council [NCR], 2001) that ground them. Furthermore, there is a growing body of research (e.g., Riordan & Noyce, 2001;Senk & Thompson, 2003) indicating that students in classrooms that utilize reform curricula (e.g., aligned to NCTM Standards) not only perform as well on standardized tests as do their counterparts in more traditional programs, but also outperform these same students on tests measuring conceptual understanding, applications, and problem-solving ability (Schoenfeld, 2007, p. 540).…”
Section: Introductionmentioning
confidence: 99%